2020
DOI: 10.1115/1.4044997
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Computational Loss Analysis of a Compressor for Heavy Duty Truck Engine Turbochargers

Abstract: This paper presents a detailed loss analysis of a centrifugal compressor stage with a vaned diffuser for application in a heavy-duty engine turbocharger. The analysis is carried out in order to investigate the loss distribution in the stage. To quantify the impact of different loss types and locations, a detailed validated steady-state three-dimensional (3D) computational fluid dynamics (CFD) solution is employed. The local entropy production rate is calculated for two operating points (full load and part load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…In their CFD study, Sun et al 48 also found higher compressor efficiency, when the wheel backside cavity was neglected. Further, the 3D computational loss analysis by Abel et al 5 reported that the wheel backside cavity losses raised with increase in mass flow rate and contributed to about 6%–7% on the total pressure losses. However, the main focus of the present study is to evaluate the effect of roughness level of the housing on the compressor performance.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In their CFD study, Sun et al 48 also found higher compressor efficiency, when the wheel backside cavity was neglected. Further, the 3D computational loss analysis by Abel et al 5 reported that the wheel backside cavity losses raised with increase in mass flow rate and contributed to about 6%–7% on the total pressure losses. However, the main focus of the present study is to evaluate the effect of roughness level of the housing on the compressor performance.…”
Section: Resultsmentioning
confidence: 99%
“…The CFD predictions of Javed and Kamphues 25 reported a reduced performance with volute surface roughness because of additional flow blockage and increased meridional velocity. Also, the loss analysis by Abel et al 5 described that circa half of the volute losses were because of friction in the housing surfaces.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations